Model hubungan bakat kepimpinan dengan kepimpinan dan hala tuju sekolah graduan program kelayakan profesional kebangsaan bagi pemimpin pendidikan (NPQEL) / S. Sathiyabama Suprammaniam - S. Sathiyabama, Suprammaniam (2017)
The Malaysian Education Blueprint (PPPM) 2013-2025 has been emphasising the appointment of principals or head teachers where their appointment is no longer based on length of service. To ensure that the appointed school leaders have high leadership potential, school leaders are exposed to training and professional development program, known as National Professional Qualification for Educational Leaders (NPQEL). NPQEL program graduates who successfully complete the compulsory courses should be able to lead the school. The Direction of School Leadership is one of the standards used by the School Inspectorate under Ministry of Education to measure the level of school excellence. Previous studies only looked at the effectiveness of NPQEL but not about their level of leadership talent. Accordingly, a quantitative survey used to identify the level of NPQEL graduates' leadership talent in line with the direction of school leadership. A total of 363 school leaders who have successfully completed the course and have served as school administrators for more than two years were selected as the respondents. Findings of descriptive statistics show that NPQEL graduates’ level of direction of school leadership and leadership talent are at high levels. Results of inferential analysis using Pearson correlation test indicates a significant and strong relationship between leadership talent with the direction of school leadership. Stepwise regression was used to check the most dominant dimensions of leadership talent in the direction of school leadership, and it was found that dimension of relationship contributed 72.0% of variance towards the direction of school leadership. The results of the t-test indicated that only school category differs significantly for the direction of school leadership scores and leadership talent scores. The t-test result also shows that primary school leaders with NPQEL have higher mean scores for both leadership talent and the direction of school leadership compared to their counterparts in the secondary schools. Finally, the proposed model was clearly demonstrated as fitting for the study population by using Structural Equation Modelling (SEM).